(untitled) (African Journal of Biomedical Research, 2021)
Breast cancer remains a global public health problems and natural products are increasingly being explored in search of new therapeutic agents with scientific evidence. This study investigated phytochemical composition, antioxidant and anti-proliferative activities of different solvent fractions of Rauvolfia vomitoria, Calliandra portoriscensis, and Anthocleista djalonensis in estrogen receptor positive MCF-7 breast cancer cell line ex vivo. Liquid-liquid chromatographic separation technique was used to obtain the chloform, ethylacetate and aqueous fractions Rauvolfia vomitoria, Calliandra portoriscensis, and Anthocleista djalonensis from their crude methanolic extractis. Qualitative and quantitaitve phytochemical analysis were performed to determine the levels of total phenolics and flavonoids. Antioxidant activities of each extract fraction were determined using the DPPH and NO scavenging assays. The MCF-7 cell line was cultured in DMEM medium overnight, exposed to difere nt concentrations (10-50 mg/mL) of each fraction for 48 h and growth inhibition was subsequently evaluated using the MTT assay. Phytochemical analysis revealed the presence of alkaloids, flavonoids, tannins and phenols in the plants. The extract fractions of C. portoriscensis, R. vomitoria and A. djalonensis at 10, 20, 30, 40 and 50 ug/mL were found to scavenge DPPH free radical dose-dependently by 7.5 – 10.2%, 11.2 – 24.9%, 17.5 – 31.8 %, 27.8 – 47.1 % and 37.8 – 62.1%. The highest DPPH scavenging activity of 62.1%, 55.4% and 54.2% was elicited by the chloroform fractions of A. djalonensis and C. portoriscensis and ethylacetate fraction of R. vomitoria at 50 mg/mL Dose-dependent NO inhibition was also observed with the highest NO inhibition elicited by R. vomitoria chloroform fraction (61.7%), followed by A. djalonensis ethylacetate fraction (55.9%) and C. portoriscensis chloroform fraction (49.6%) at 50 mg/mL the extract fractions also induced anti-proliferative effects on MCF-7 cell in a dose-dependent manner and significantly (P<0.05) with maximum elicitation observed at 96 h post treatment. On the whole, only the chloroform extract fraction of A. djalonesis elicited moderate anti-proliferative potency against MCF-7 cell line with an IC50 of 66.8 + 8.3 mg/mL, while other extract fractions have low to no potency with IC50 range of 237.4 – 605.7 mg/mL Unlike cisplatin (IC50 of78.4 – 108.3 mg/mL,), the proliferation of the normal Vero cell lines was less affected by the extract fractions (IC50 237.4 – 605.7 mg/mL) . Findings in this study provide scientific evidence for chloroform fraction of Anthocleista djalonensis as a potential source of novel therapeutic agents for future breast cancer pharmacotherapeutic explorations.